Training on Portioning Standards and Food Management in Daycare Centers in Bandung City - Mutiara Santanu, Ayu; Fitrianingsih, Asti Dewi Rahayu; Septia Rosdiana, Delita (LP2M INSURI Ponorogo, 2025)
Daycare is one of the places that has an important role in supporting children's growth and development, including ensuring children's nutritional intake is appropriate for their age. However, the current quality of daycare centers has not reached the appropriate level. Thus, assisting and increasing caregiver knowledge and skills on organizing a good meal is necessary. This community service program aims to improve the ability of caregivers to calculate nutritional intake according to children's needs and to properly manage the organization of meals in daycare. The method used in this program is a quasi-experiment, which provides training and assistance in preparing lunch menus and morning/afternoon snacks based on local foods. The results of the service program showed that 78.6% of caregivers stated that they were satisfied with the help provided by lecturers and female students during the daycare food menu cooking training, 85.7% of caregivers stated that the food menu made was easy to apply in their workplaces, and 92.9% of caregivers stated that the training provided was by their needs and wanted similar training again. This program can be an effective alternative to increase caregivers' knowledge in Daycare in preparing menus according to the nutritional needs of children.